EXPERIENCE OF PATIENTS WITH CHRONIC DISEASES IN COMPLEMENTARY MEDICINE AND INTEGRATIVE HEALTH SEEKING BEHAVIORS - Eza Kemal Firdaus; Widyawati Widyawati; Cristantie Effendy (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2021)
Background: Chronic diseases, including heart disease, cancer, COPD, and DM, are the main causes of death worldwide. Nearly half of all global deaths are caused by such diseases. Complementary medicine and integrative health are believed to have great potential in providing benefits to public health. This research aims to determine the experience of patients with chronic diseases in seeking for complementary medicine and integrative health. Method: This research is a qualitative research with a phenomenological approach. The data collection method used is the in-depth interview with 8 patients with chronic diseases (heart disease, cancer, COPD, and DM). Result: In this study there were 5 themes found related to the experience of patients with chronic diseases in the behavior of seeking complementary medicine and integrative healthcare which includes economic factors and doubts to the conventional medicine, as well as the values of traditional medicine that were being the reasons in the process of seeking complementary medicine and integrative healthcare. Seeking the Complementary medicine and integrative healthcare is strongly influenced by support of family, community, and social media. That suggest more positive than the negative impacts after undergoing the complementary medicine and integrative healthcare. Participants perception that traditional medicine is better than the conventional one. Closed minded participants to seek to doctors after undergoing the traditional medicine. Conclusion: Besides as a medical treatment, the use of traditional medicine for patients with chronic diseases also manifests the beliefs of patients that need to be facilitated by providing assistance hoping that possible dangerous risks can be avoided.